Effect of Physical and Chemical Treatment on the Characteristics of Wheat Straw as Fuel for Energy Applications - Noha Said; Raid Alrowais; Mahmoud Abdel-Daiem (BioResources, 2024)
The use of wheat straw as a renewable energy source is essential from both energy production and environmental points of view. It has a great energy potential that can be generated either by combustion or anaerobic digestion. However, there are some limitations during its conversion to energy in both techniques. Therefore, the current study investigated the effect of physical and chemical treatments on the characteristics of wheat straw as fuel for energy applications. Water washing of wheat straw and mixing with KOH solution were applied for physical and chemical treatments. Physical, chemical, and thermal characteristics of wheat straw were investigated before and after the treatments. It was found that the wheat straw has high carbon (44.8%) and volatile contents (87.1%), making it an excellent source for energy production. The physical treatment showed a positive impact on reducing the ash content (by 14.9%) and undesirable compounds, such as K and Cl, which were reduced by 46.4% and 57.0%, respectively. Moreover, it reduced sintering formation through combustion. In contrast, the chemical treatment resulted in 9.3% lignin removal and destroyed the complex lignocellulosic structure, thereby increasing the cellulose accessibility and enhancing the anaerobic digestion process. Therefore, the applied treatments showed attractive options to solve problems related to straw energy generation.